Notes on John Cage and literature (2019)
The present text about John Cage and literature is composed of sixteen little sections that illustrate a journey through different moments of Cage’s creative process and is related to the authors and literary works of the second half of the XIX and XX century. Finally, freedom in the creation of both the musical composition and literary work and the different meanings that it can take are examined.